Wolves - Simon, Seymour ([New York, N.Y.] : HarperCollins, 1993)
Text and photographs present the physical characteristics, habits, and natural environment of various species of wolves.
Elem. School Library Collection.
Wilson's Children.
Wilson's Junior High School.
5.5
4-6
K-3
Keywords: Wolves -- Juvenile literature; Wolves; Wolves